Bridging Generational Differences in Family-Owned Business: Enhancing Employee Performance Among Millennials and Generation Z Through Job Satisfaction - Fahrulia Emeralda; Achmad Ghazali (Jurnal Pendidikan Indonesia, 2025)
This study examines the relationship between Millennials and Generation Z Characteristic, Family Business Culture, and Employee Performance, with Job Satisfaction as a mediating variable. The study use Keke Busana an established family-owned fashion business in Indonesia, as a case study. The study addresses the challenges brough by the distinct preferences of generations, particularly for Millennials and Generation Z who are now dominating the workforce, accounted for 53.81% out of the total Indonesian’s workforce. Through the use of quantitative approach, data were gathered using survey questionnaires distributed to 110 Millennials and Generation Z employees of Keke Busana. The data collected were analyzed using the Structural Equation Modeling (SEM-PLS) to explore the complex correlation between the latent variables. The research aims to find out the best strategies for family businesses like Keke Busana to maximize their human resource, especially leveraging the strengths Millennials and Generation Z. The result shows positive correlation between variables, highlighting the importance of providing work-life balance, growth opportunities, company’s ability to adapt to work environment to generational preferences in order to enhance job satisfaction that has high significance to overall employee performance and productivity. However, despite the positive relationships, the result shows that there is not significant relationship between Millennials and Generation Z to employee performance, meaning that these traits do not independently drive positive influence in employee performance. Further, the study recommends actionable strategic action for family-owned businesses to manage generational diversity, foster collaboration, and achieve sustainable long-term success.